Identity Safety Cues Predict Instructor Impressions, Belonging, and Absences in the Psychology Classroom - Howansky, Kristina; Maimon, Melanie; Sanchez, Diana (Teaching of psychology, 2022)
Background: Students with marginalized identities report a lack of cultural competence among faculty in higher education classrooms. Identity safety cues (ISCs) signal to minority group members that their identities are valued and respected. Objective: The purpose of this study was to test for differences in students’ perceptions of their professor, sense of belonging, and academic outcomes when comparing an ISC course with a control course. Method: We randomly assigned one of two sections of a large social psychology course to receive ISCs while the other section was taught in a control format. The same professor taught both sections. Results: Participants in the ISC class believed their professor was trying to create an inclusive classroom and disapproved of social inequalities more than participants in the control course. These students also reported a higher sense of belonging and fewer absences. Conclusion: ISCs were associated with favorable impressions of faculty, a sense of belonging in the classroom, and fewer absences. Teaching Implications: Professors can make small adjustments to signal identity safety in their classrooms. These ISCs may foster a sense of belonging and motivation to attend the class for learners with diverse identities.